2005
DOI: 10.1093/aje/kwi329
|View full text |Cite
|
Sign up to set email alerts
|

Model of Risk of Cortical Cataract in the US Population with Exposure to Increased Ultraviolet Radiation due to Stratospheric Ozone Depletion

Abstract: The authors modeled the possible consequences for US cataract incidence of increases in ultraviolet B radiation due to ozone depletion. Data on the dose-response relation between ocular exposure to ultraviolet B radiation and cortical cataract were derived from a population-based study (the Salisbury Eye Evaluation Project, Salisbury, Maryland) in which extensive data on cataract and ultraviolet radiation were collected in persons aged 65-84 years. Exposure estimates for the US population were derived using es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 23 publications
2
37
0
3
Order By: Relevance
“…Presently, the depletion of the stratospheric ozone layer remains a major concern (UNEP, 1998;UNEP 2002). West et al (2005) modeled the possible consequences for US cataract incidence of increases in ultraviolet B radiation owing to ozone depletion. Their analysis indicated that by 2050, the prevalence of cortical cataract will increase above expected levels by 1.3-6.9%.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the depletion of the stratospheric ozone layer remains a major concern (UNEP, 1998;UNEP 2002). West et al (2005) modeled the possible consequences for US cataract incidence of increases in ultraviolet B radiation owing to ozone depletion. Their analysis indicated that by 2050, the prevalence of cortical cataract will increase above expected levels by 1.3-6.9%.…”
Section: Introductionmentioning
confidence: 99%
“…15 Henceforth, if the anti-oxidative function is maleficent at a younger age, EOC may occur because ROS-damaged DNA cannot be repaired, leading to a higher cancer possibility in young adults.…”
Section: Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…22 In that study, using a hat or sunglasses was associated with decreased risks of nuclear and cortical opacities in women and men but the associations were modest and not statistically significant. Nevertheless, if West et al 23 are correct in their assumptions, the effect of ozone depletion and resultant increased exposure to UV-B may result in a sizable increase in the number of persons with cortical cataract. In the face of these data and predictive models, even if imperfect, the use of hats with brims and protective (against UV-B) lenses may be warranted as an approach to reduce the risk of cataract.…”
Section: Light Exposurementioning
confidence: 99%